2022
DOI: 10.1186/s12920-022-01227-7
|View full text |Cite
|
Sign up to set email alerts
|

Atypical deletion of Williams–Beuren syndrome reveals the mechanism of neurodevelopmental disorders

Abstract: Genes associated with specific neurocognitive phenotypes in Williams–Beuren syndrome are still controversially discussed. This study identified nine patients with atypical deletions out of 111 patients with Williams–Beuren syndrome; these deletions included seven smaller deletions and two larger deletions. One patient had normal neurodevelopment with a deletion of genes on the distal side of the Williams–Beuren syndrome chromosomal region, including GTF2I and GTF2IRD1. However, another patient retained these g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Another BP-associated candidate gene, FZD9, is located in the Williams syndrome (WS) deletion region; WS is a genetic neurodevelopmental disorder characterized by cognitive, behavioral, emotional and social symptoms, which is dependent on the genes involved in the deletion [30]. Research has shown that FZD9, as an important factor in neural cell regulation, is highly expressed in the hippocampus, and the deletion of the FZD9 gene could affect the development of the nervous system and cause cognitive impairment by increasing the doubling and apoptosis of nerve cells [31,32]. HTR7, associated with ST, is considered an important candidate gene because it was a candidate locus in several neuropsychiatric disorders based on pharmacological studies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Another BP-associated candidate gene, FZD9, is located in the Williams syndrome (WS) deletion region; WS is a genetic neurodevelopmental disorder characterized by cognitive, behavioral, emotional and social symptoms, which is dependent on the genes involved in the deletion [30]. Research has shown that FZD9, as an important factor in neural cell regulation, is highly expressed in the hippocampus, and the deletion of the FZD9 gene could affect the development of the nervous system and cause cognitive impairment by increasing the doubling and apoptosis of nerve cells [31,32]. HTR7, associated with ST, is considered an important candidate gene because it was a candidate locus in several neuropsychiatric disorders based on pharmacological studies [33].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been revealed that native vesicle docking can be mediated by a single trans binary Sx1A-Sb2 complex in the absence of SNAP25 [ 39 , 40 ]. And STX1A may be involved in Williams-Beuren syndrome and Parkinson's disease [ 41 , 42 ]. To date, the link between STX1A and dopaminergic neurons is not fully disclosed.…”
Section: Discussionmentioning
confidence: 99%
“…Given the complexity of cancer etiology and unsatisfactory treatment outcomes, it is imperative to explore the role of more genes in pan-cancer. BAZ1B has been reported to maintain chromosomal structural stability, participate in neurodevelopment, and be involved in cellular biological processes such as chromosomal remodeling, transcriptional regulation, DNA repair [31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%